Morphology controlled synthesis of LiV(2)0(5)/Ag nanocomposite nanotubes with enhanced electrochemical performance - Diggikar, Rahul S.; Dhavale, Vishal M.; Shinde, Dhanraj B.; Kanbargi, Nihal S.; Kulkarni, Milind V.; Kale, Bharat B. (RSC Advances, 2012)
Uniformly embedded silver (Ag) nanoparticles in orthorhombic nanotubes (NTs) of lithium vanadium oxide (LVO) synthesized via a facile template-free hydrothermal treatment at low temperature exhibited an excellent morphology with good crystallinity and may act as an exceptional contender for electronic applications.